Facebook, Twitter and Google Plus for Breaking News: Is There a Winner? - Osborne, Miles; Dredze, Mark (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
Twitter is widely seen as being the go to place for breaking news.Recently however, competing Social Media have begun to carry news.Here we examine how Facebook, Google Plus and Twitter report on breaking news. We consider coverage (whether news events are reported) and latency (the time when they are reported). Using data drawn from three weeks in December 2013, we identify 29 major news events, ranging from celebrity deaths, plague outbreaks to sports events. We find that all media carry the same major events, but Twitter continues to be the preferred medium for breaking news, almost consistently leading Facebook or Google Plus. Facebook and Google Plus largely repost newswire stories and their main research value is that they conveniently package multitple sources of information together.